The Effect of Service Quality on Patient Loyalty evidence from Privat Hospitality - Nora Asriani (Journal of Applied Business, Taxation and Economics Research, 2023)
This study aims to investigate the effect of service quality on patient loyalty in private hospitals. The population in this study were all patients at Krakatau Medika Hospital. The samples used were outpatient and inpatient patients with purposive sampling as a data collection technique. the test results show that all dimensions of service quality affect patient loyalty.